2013
DOI: 10.7309/jmtm.2.4s.2
|View full text |Cite
|
Sign up to set email alerts
|

Improving recognition of severe illness and patient pathways in primary health services using mHealth technology in urban Blantyre, Malawi

Abstract: Hospital-based studies suggest that late presentation at tertiary level is a driving factor for mortality from severe febrile illness in resource-poor contexts. Recent research into health seeking pathways in Malawi identified primary level barriers linked to service provision and misdiagnoses. In Malawi an Emergency Triage, Assessment and Treatment (ETAT) package, approved by the World Health Organisation (WHO) has been introduced at tertiary level and is being rolled out to district and primary clinics. mHea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Malawi, ETAT has been implemented in tertiary and secondary hospitals [ 16 ], with discussions about integration with the IMCI programme and roll-out to primary care at the time of the study [ 17 ]. A pilot study in peri-urban primary care in Malawi suggested implementation is feasible and increased accuracy of referrals; however, this study used a digital tool with decision support [ 18 , 19 ]. Given primary care facilities are mostly staffed by lower cadres of healthcare workers and varying resources, assessing the current capacity to deliver ETAT in this context is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In Malawi, ETAT has been implemented in tertiary and secondary hospitals [ 16 ], with discussions about integration with the IMCI programme and roll-out to primary care at the time of the study [ 17 ]. A pilot study in peri-urban primary care in Malawi suggested implementation is feasible and increased accuracy of referrals; however, this study used a digital tool with decision support [ 18 , 19 ]. Given primary care facilities are mostly staffed by lower cadres of healthcare workers and varying resources, assessing the current capacity to deliver ETAT in this context is needed.…”
Section: Introductionmentioning
confidence: 99%